REVISITING CLASSICAL ORGANIZATIONAL COMMUNICATION THEORIES IN CONTEMPORARY ORGANIZATIONS: A CRITICAL REVIEW OF SCIENTIFIC MANAGEMENT, HUMAN RELATIONS, AND BUREAUCRATIC THEORIES - Nesa Fatma Melisa Ritonga; Fadhillah Nur Annisaa; Nadya Rahmatika Ghania Mahidh (OPINI: Journal of Communication and Social Science, 2026)
This article critically examines the development and contemporary relevance of three classical organizational communication theories: Scientific Management, Human Relations, and Bureaucratic Theory. Using a qualitative library research approach with a structured critical literature review, the study analyzes selected scholarly sources to compare the historical foundations, communication assumptions, epistemological contributions, and limitations of each theory. The findings show that the development of organizational communication theory is not a simple linear shift from one perspective to another, but a continuing interaction among three analytical logics: control, participation, and formal legitimacy. Scientific Management frames communication as an instrument of efficiency and supervision, Human Relations emphasizes interpersonal interaction and employee participation, and Bureaucratic Theory highlights communication as a mechanism of procedural order and accountability. The study concludes that these classical theories remain relevant in contemporary, digital, and post-bureaucratic organizations because they continue to explain how organizations negotiate ongoing productivity, collaboration, and institutional structure today.